The influence of heat transfer conditions on the parameters characterizing the ignition of coal-water fuel particles; Thermal Engineering; Vol. 62, iss. 10 - Syrodoy S. V. Semen Vladimirovich (Steam Boilers, Power Plant Fuel, Burner Arrangements, And Auxiliary Equipment Of Boilers, 2015)
Title screen